FAKTORâFAKTOR YANG BERPENGARUH TERHADAP STRUKTUR MODAL (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar Di BEI Tahun 2011-2013) - Fitria Fachrunnisa, 11.05.52.0062; Badjuri, Achmad (Students Journal of Accounting and Banking, 2015)
This study aims to examine the effect of Profitability, Current Ratio, AssetStructure, Non-Debt Tax Shield, Sales Growth to Capital Structure in Manufacturing Company listed on the Indonesia Stock Exchange period 2011-2013. The sample that used in this study are Manufacturing Company that listed in Indonesia Stock Exchange period 2011-2013. The sampling method used in this study was purposive sampling. The number of sample that used 77 companies. Data analysis used linear regression berganda Ordinary Least Squares (OLS). The results of this study find that the Profitability, Current Ratio, Stucture Asset variable have significant negative effect to structure of capital, the Non-Debt Tax Shield has significant negative effect to structure of capital, Sales Growth has significant positive effect to structure of capital.Keywords: Structure of Capital, Profitability, Current Ratio, Asset Structure, Non- Debt Tax Shield, and Sales Growth